Analisis Wacana Sara Mills dalam Film Serendipity - Nurussaadah, Erfina; Yudhawirawan, Radhi Abimanyu (Fakultas Ekonomi dan Ilmu Sosial Program Studi Ilmu Komunikasi Universitas AMIKOM Yogyakarta, 2023)
The Serendipity film is a film by Indra Gunawan which was released in 2018. The film has a storyline in the form of issues regarding bullying in adolescents, especially young girls. Not only bullying but in this film there is an issue regarding gender equality between women and men. Based on the background above, the formulation of the problem in this thesis is how the position of the subject-object describes the position of bullying against women in the film Serendipity and how the position of the reader or viewer describes the position of bullying against women in the film Serendipity.The method used by researchers in this study is a Sara Mills' Critical Discourse Analysis. This method has a focus on feminist discourse such as how women are shown in text, pictures, photos and news. This research is reviewed from the position of the subject-object and the position of the reader. The data used in this study are several scenes in the Serendipity film. The results of this study conclude that based on the theory used in this study, namely Sara Mills' Critical Discourse Analysis, the character Rani has a depiction of an oppressed female student, and this analysis focuses on the depiction of women shown in the film Serendipity. Therefore, what Sara Mills does is often referred to as a feminist perspective. The point of concern from the perspective of feminist discourse is to show how the text is biased in presenting women as the wrong party.